Writing workshop : - Blanton, Linda Lonon (Heinle & Heinle Publishers, 1998)
Writing Workshop is a fully-integrated reading and writing program that reviews and consolidates the critical literacy skills that ESL and developmental learners will need as they transition to mainstream academic classes. By providing students with authentic texts, assignments, samples of responses to assignments, users of Writing Workshop write, read, and discuss their way into mainstream academic study.